2020
DOI: 10.22336/rjo.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between corneal biomechanics and specular microscopy in patient with cataract

Abstract: This study aimed to analyze the connection between corneal biomechanics (corneal hysteresis, CH) and endothelial cell density of cornea (mean endothelial cell density, MCD) in patients diagnosed with cataract. This retrospective, observational study was performed in the Ophthalmology Clinic of the University Emergency Hospital in Bucharest. Of 60 patients (120 eyes) with cataract, who were included in this study, we analyzed the CH values obtained using with the Ocular Response Analyzer (ORA) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(22 reference statements)
0
0
1
Order By: Relevance
“…Our study has found statistically significant, moderate-to-strong correlations between CH and CRF and endothelial cell count and variability. However, to the best of our knowledge, these findings differ from those in the literature, where no significant correlation has been found between biomechanical and endothelial corneal parameters in healthy volunteers [ 39 ] or in patients with cataract [ 40 ]. As the level of corneal hydration, which is regulated by the endothelial pump function, may influence corneal biomechanics [ 39 ], more studies are needed in order to identify the factors that modulate the relationship between CH, CRF and endothelium parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study has found statistically significant, moderate-to-strong correlations between CH and CRF and endothelial cell count and variability. However, to the best of our knowledge, these findings differ from those in the literature, where no significant correlation has been found between biomechanical and endothelial corneal parameters in healthy volunteers [ 39 ] or in patients with cataract [ 40 ]. As the level of corneal hydration, which is regulated by the endothelial pump function, may influence corneal biomechanics [ 39 ], more studies are needed in order to identify the factors that modulate the relationship between CH, CRF and endothelium parameters.…”
Section: Discussioncontrasting
confidence: 99%